Effectiveness of tramadol or topic lidocaine compared to epidural or opioid analgesia on postoperative analgesia in laparoscopic colorectal tumor resection - Spindler-Vesel Alenka; Jenko Matej; Repar Ajsa; Potocnik Iztok; Markovic-Bozic Jasmina (Radiology and Oncology)
Chronic postoperative pain is the most common postoperative complication that impairs quality of life. Postoperative pain gradually develops into neuropathic pain. Multimodal analgesia targets multiple points in the pain pathway and influences the mechanisms of pain chronification.